2015
DOI: 10.1103/physrevb.92.195204
|View full text |Cite
|
Sign up to set email alerts
|

Quantitatively analyzing phonon spectral contribution of thermal conductivity based on nonequilibrium molecular dynamics simulations. I. From space Fourier transform

Abstract: Probing detailed spectral dependence of phonon transport properties in bulk materials is critical to improve the function and performance of structures and devices in a diverse spectrum of technologies. Currently, such information can only be provided by the phonon spectral energy density (SED) or equivalently time domain normal mode analysis (TDNMA) methods in the framework of equilibrium molecular dynamics simulation (EMD), but has not been realized in non-equilibrium molecular dynamics simulations (NEMD) so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 54 publications
3
38
0
Order By: Relevance
“…Therefore, only the small region near the sample affects the simulation results. This phenomenon is consistent with the findings in previous studies in which the length of the thermal reservoirs did not influence the results when it exceeded a critical value, which depended on the time parameter of the thermostat [24,32,37]. In contrast, for the NHC thermostat in Fig.…”
Section: The Effects Of Thermal Reservoir Size and Boundarysupporting
confidence: 92%
“…Therefore, only the small region near the sample affects the simulation results. This phenomenon is consistent with the findings in previous studies in which the length of the thermal reservoirs did not influence the results when it exceeded a critical value, which depended on the time parameter of the thermostat [24,32,37]. In contrast, for the NHC thermostat in Fig.…”
Section: The Effects Of Thermal Reservoir Size and Boundarysupporting
confidence: 92%
“…Generally speaking, there is always length effect in NEMD simulations, since the long mean free path phonons are truncated by the length boundaries and contribute little to the overall thermal conductivity 35 . For NWs with cross-sections of a few nanometers, the mean free path (MFP) is only several nanometers 36 .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…F. Alvarez et al 50 considered the size effect via doing the moment expansion of linearized Boltzmann transport equation in the relaxation time approximation, and found that the effective thermal conductivity will increase and then converge with the effective length. In the system with small effective length (dozens of nanometers in our paper), the thermal conductivity will be size dependent due to the fact that the phonons with MFP larger than the system will be truncated and have no contribution to the total thermal conductivity 35 . Recently, Hua and Cao 51 generated a theory based on the phonon BTE to study the influence of boundary constraints on thermal conductivity of NWs.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Molecular dynamics simulations [7,8] have allowed the overall value of the TBR to be computed, including the full anharmonicity of the interatomic potential. Mode-resolved techniques [9][10][11][12][13][14] were recently developed to investigate how specific phonon modes are affected by interfaces. However, the typical wave packet approach is extremely computationally expensive for many modes in a Brillouin zone grid.…”
Section: Introductionmentioning
confidence: 99%